The health economics burden of sarcopenia: a systematic review - Bruyère, Olivier; Beaudart, Charlotte; Ethgen, Olivier; Reginster, Jean-Yves; Locquet, Médéa (Maturitas, 2019)
•Our systematic review found 14 studies that compared the healthcare costs of treating sarcopenic and non-sarcopenic patients.•Eleven of these studies showed higher healthcare costs for sarcopenic patients than for non-sarcopenic patients.•These studies were very heterogeneous regarding populations and settings, the assessment of sarcopenia and the type of costs evaluated.•Most of the included studies showed methodological bias, especially the absence of adjustment for important confounding variables.•More well designed studies are needed before it can be concluded that sarcopenia increases healthcare costs. Despite of better knowledge about sarcopenia, an optimal understanding of its consequences from a public health perspective remains a challenge. Specifically, the economic burden of the illness is unclear. As a support for the public health policy makers and other health actors, our objective was to perform a systematic review of the literature comparing healthcare costs between sarcopenic and non-sarcopenic patients (under the registration number CRD42018099291). A search for relevant articles was conducted on the Medline and Scopus databases. Rigorous eligibility criteria were established (e.g., subjects with sarcopenia, both men and women, mean age of the sarcopenic population) and applied by two investigators to identify suitable studies. The first screening phase, performed by 2 independent reviewers, covered 455 references. Fourteen relevant studies were included in the final analysis. Overall, we noted an important heterogeneity between studies in the way of assessing sarcopenia (i.e. operational definitions, tools and cut-offs used). There were also large variations between studies in their cost analysis settings (i.e., discrepancies in time horizon, types and sources of economic data). Most of the studies focused on hospitalization costs following surgery for a specific disease such as cancer. Finally, 11 out of the 14 studies reported higher healthcare costs for sarcopenic patients. However, most of the included studies have important methodological bias (e.g. potential confusion factors rarely taken into account), and low to moderate quality scores. More standardized research, taking into account all the limitations of the published studies, should be conducted to assess the true impact of sarcopenia on healthcare consumption.